ANALISIS PENGARUH KUALITAS AUDITOR, LIKUIDITAS, PROFITABILITAS, SOLVABILITAS, DAN PERTUMBUHAN PERUSAHAAN TERHADAP OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2016 - Sri Ernita; M Rasuli; Julita Julita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to determine and analyze the influence of auditor qualits, liquidity, profitability, solvency and corporate growth on the provision of Going Concern audit opinion on manufacturing companies listed on the Stock Exchange Iindonesia. The method used in this research is to use descriptive and quantitative methods of collecting the necessary data that comes from the company and then describe it as a whole that will provide an overview of the research results. The sample of research is manufacturing company listed in Indonesia Stock Exchange (BEI) during 2012-2016 is as many as 77 companies with company criteria that presents complete financial statements. The data used in this research is secondary data. Data analysis method that will be used is Logistic Regression Analysis Method, because the data used in this research is a variable that is nonmetric or nominal. The result of the research shows that descriptive statistic analysis to manufacturing industry company shows that from 385 sample companies that are categorized receive going concern audit opinion as many as 176 sample companies while those who do not accept going concern audit opinion 209 sample companies. The result of test by using logistic regression shows that the variable of liquidity ratio, profitability, company growth, and audit quality do not have an effect on acceptance of going concern audit opinion at 5% significance level. Testing using logistic regression showed that variable solvency ratio had an effect on acceptance of going concern audit opinion at 5% significance level.Keywords : Going Concern Audit Opinion, Auditor Quality, Liquidity, Profitability, Solvency, and Corporate Growth